Breast-conserving therapy and modified radical mastectomy for primary breast carcinoma: a matched comparative study - Wang, Lize; Ouyang, Tao; Wang, Tianfeng; Xie, Yuntao; Fan, Zhaoqing; Lin, Benyao; Li, Jinfeng (Chinese Journal of Cancer Research; Vol 27, No 6 (December 22, 2015): Chinese Journal of Cancer Research, 2015)
Objective: To compare two types of therapy for primary breast carcinoma, breast-conserving therapy (BCT) and modified radical mastectomy (MRM), in a matched cohort study. Methods: A series of 1,746 patients with primary breast cancer treated with BCT or MRM in a single Chinese institute between January 2000 and February 2009 were analyzed retrospectively to compare their outcomes with respect to the incidence of local recurrence (LR), distant metastasis, and survival. The patients were matched with regard to age at diagnosis, spreading to axillary lymph nodes, hormone receptor status, the use of neoadjuvant chemotherapy and maximal tumor diameter. The match ratio was 1:1, and each arm included 873 patients. Results: The median follow-up period was 71 months. The 6-year disease-free survival (DFS) and 6-year distant disease-free survival (DDFS) rates differed significantly between two groups. The 6-year local recurrence-free survival (LRFS) rates were 98.2% [95% confidence interval (95% CI): 0.973-0.989] in the BCT group and 98.7% (95% CI: 0.980-0.994) in the MRM group (P=0.182), respectively. DFS rates in BCT and MRM groups were 91.3% (95% CI: 0.894-0.932) and 86.3% (95% CI: 0.840-0.886) (P